Fabrication of Sm2O3 nano-particle – Transparent urethane resin composite films and its PL properties - Yamada, Katsumi; Miyazaki, Hidetoshi (Optical materials, 2021)
Using a solution of samarium nitrate and ethanol and a UV-curable liquid urethane resin as starting materials, we fabricated samarium (III)oxide (Sm2O3) nanoparticle-based composite films. The color of the films turned from yellow (of the precursor) to reddish orange after being cured by UV irradiation. The particle size of the Sm2O3 in the composite film were measured using transmission electron microscopy (TEM) and observed to be in the range of 56–86 nm. Moreover, the crystallographic structure of the particles was analyzed via TEM and selected area electron diffraction. The composite film exhibited photoluminescent (PL) properties with a peak at 640 nm (corresponding to the transition 4G5/2 → 6H9/2) upon irradiation with light at a wavelength of 340 nm. Furthermore, upon extended UV light irradiation, some of the trivalent Sm3+ of Sm2O3 particles in the films were reduced to Sm2+, which was confirmed by the PL peaks observed at 683 nm and 731 nm (attributed to the divalent Sm2+). [Display omitted] •The Sm2O3-based urethane resin matrix composite film was fabricated using Sm(NO3)3 solution and translucent urethane resin.•Crystalline Sm2O3 nano-particles (56–86 nm) were observed in the resulting composite films by TEM and TEM-ED measurements.•The composite film showed PL properties with the peaks derived from Sm3+ ions and Sm2+ ions by UV irradiation at 340 nm.•We have successfully fabricated Sm2O3 based red PL composite materials.